Funcionalização de nanotubos de carbono de dupla camada com aminoácido lisina: uma abordagem de primeiros princípios - Silva, José Edilson Costa da (2009)
In this work we studied the adsorption and the encapsulation of the amino acid lysine with the double wall carbon nanotube (DWCNT) (8,0)@(17,0). This study is of interest for applications technological, because it allows to analyze the carbon nanotubes in di erent atmospheres and also to give it the speci c functions with biological goals. To treat with details the properties structural and electronics of the considered system, we used one theoretical approach based on calculations of rst principles making use of the density functional theory with the approach of the generalized gradient to describe the exchange and correlation term. The calculations were accomplished using the program SIESTA. When the system reached the expected convergence, the analysis of electronic properties through the structure of the band and density of states showed signi cant changes in behavior of system. System (8,0)@(17,0) DWCNT with lysine interacting on the outer wall begins to show character metallic, while the system with the lysine encapsulated energy gap is 0.30 eV to 0.19 eV. Also the degenerate levels of the system pure lose the degeneration when amino acid lysine is adsorbed and also encapsulated in DWCNT. To check the stability of these systems, we calculate the binding energy, which has a value of -1.63 eV indicating that this system is highly stable, while the (8,0)@(17,0) DWCNT with lysine encapsulated has a binding energy of the order of 3.24 eV, indicating the low stability.